Consumption of a diet rich in Brassica vegetables is associated with a reduced abundance of sulphate‐reducing bacteria: A randomised crossover study. Issue 9 (12th April 2017) - Kellingray, Lee; Tapp, Henri S.; Saha, Shikha; Doleman, Joanne F.; Narbad, Arjan; Mithen, Richard F.
Abstract : A randomised crossover study was performed with ten healthy adults to examine the effects of a low‐ and high‐ Brassica diet on members of the human gut microbiota. Participants were randomised to the low–high or high–low diets, with a 2‐wk washout period separating the diets. The low‐ Brassica diet consisted of two portions of Brassica foods across 2 wk, and the high‐ Brassica diet contained 18 portions over 2 wk. The Brassica ‐rich diet was associated with a reduction in the relative abundance of sulphate‐reducing bacteria, which have been linked to gastrointestinal disorders. Abstract : Scope: We examined whether a Brassica ‐rich diet was associated with an increase in the relative abundance of intestinal lactobacilli and sulphate‐reducing bacteria (SRB), or alteration to the composition of the gut microbiota, in healthy adults. Methods and results: A randomised crossover study was performed with ten healthy adults who were fed a high‐ and a low‐ Brassica diet for 2‐wk periods, with a 2‐wk washout phase separating the diets. The high‐ Brassica diet consisted of six 84 g portions of broccoli, six 84 g portions of cauliflower and six 300 g portions of a broccoli and sweet potato soup. The low‐ Brassica diet consisted of one 84 g portion of broccoli and one 84 g portion of cauliflower. Faecal microbiota composition was measured in samples collected following 2‐wk Brassica ‐free periods (consumption of all Brassica prohibited), and after each diet, whereby the only Brassica consumed was that supplied by the study team. No significant changes to the relative abundance of lactobacilli were observed ( p = 0.8019). The increased consumption of Brassica was associated with a reduction in the relative abundance of SRB ( p = 0.0215), and members of the Rikenellaceae, Ruminococcaceae, Mogibacteriaceae, Clostridium and unclassified Clostridiales ( p < 0.01). Conclusion: The increased consumption of Brassica vegetables was linked to a reduced relative abundance of SRB, and therefore may be potentially beneficial to gastrointestinal health.